FINANCIAL FRAUD AND SECURITY (INNOVATIVE ECONOMY, 2021)
Honchar L.V., Malakhova A.V., Nevkypila O.S. FINANCIAL FRAUD AND SECURITYPurpose. The aim of the study is to characterize the features of financial fraud in enterprises and in people’s lives, to identify identification criteria and substantiate practical recommendations for ways to minimize it in modern conditions.Methodology of research. The methodological basis of the study was scientific methods of cognition, based on a systematic approach to solving problems. A number of general and special scientific research methods were used to achieve this goal and obtain research results: dialectical; monographic (when processing scientific publications); system analysis (in the study of types of financial fraud and security of the population); method of analogies and comparisons (in the study of international practice for the prevention of financial fraud); comprehensive analysis (in the formation of conclusions and proposals for solving the tasks) and others.Findings. The article reveals the problems of financial fraud in the current conditions of instability of Ukraine’s economy. Based on the analysis of theoretical and methodological approaches, the essence of the category "fraud" is revealed. Peculiarities of manifestation of different types of financial fraud at enterprises are given, such as: embezzlement or theft by an employee; fraud by managers or managers; investment scams; fraud on the part of suppliers; fraud on the part of the customer or client. The main methods of counteracting financial fraud at enterprises are revealed, in particular: unexpected inspection of the enterprise; legendary check; internal investigation of fraud; obtaining information from open sources. A study of the main modern types of financial fraud against individuals, in particular: social engineering; streaming; phishing; theft of a financial phone number; financial pyramids. The statistical indicators of the negative consequences of the activities of financial fraudsters in Ukraine are given. The directions of avoiding the negative consequences of illegal actions are determined, such as: non-dissemination of one’s personal data; non-disclosure of bank card information, passwords from private accounts on the bank’s website; not opening letters in the mail from suspicious addresses; careful inspection of the ATM before its use; cover the keyboard when entering the PIN code of the bank card; do not install suspicious programs; not to believe offers with earnings of super profits, etc.Originality. For the first time, a comprehensive analysis of the manifestation of various types of financial fraud was carried out and practical recommendations were substantiated on the directions of their minimization, taking into account the best foreign experience.Practical value. Proposed recommendations for combating financial fraud based on the results of the study will help to increase the level of financial security of the population of Ukraine.Key words: financial fraud, financial security, social engineering, streaming, phishing, financial pyramids.
Keywords: Key words; financial fraud; financial security; social engineering; streaming; phishing; financial pyramids.